A Dynamic Key Generation Scheme based on Metaheuristic Cuckoo Search - Sarkar, Arindam; Dey, Joydeep; Bhowmik, Anirban; Ferdows, Sk. Samim (International Journal of Computer Sciences and Engineering, 2025)
Nature inspired food foraging features by the cuckoo species promotes the proposed methodology to generate a true random session key. To make more complex for the intruders, a key based on the behavior of cuckoo species creates the fittest solution out of the sample population. Metaheuristic based optimization algorithms are good enough to encapsulate information during the wireless communication in more secured approach. Statistical fitness function ensuring with randomized expansion of bits in the session key have been tested. The key which has been generated dynamically using cuckoo search passed through different statistical tests in order to synthesize the randomness. In this paper run test is used for examining the robustness of key and test result shows the good randomness.